Effects of individual work period with metacognitive prompts on learners autonomy and concept understanding in biology - Castillo, Mary Joyce G. (College of Education, University of the Philippines Diliman, 2021)
This study examined the effects of Individual Work (IW) period with metacognitive prompts on learner autonomy and concept understanding in Biology and determined if autonomy is a positive predictor of concept understanding. It also studied the perception of participants about IW period with metacognitive prompts-a one-hour provision for independent study time wherein students are to individually complete their chosen learning task at their own pace. Metacognitive prompts were answered by the students in their journal every time they work on their biology learning task. This single group pretest-posttest study involved 64 female Grade 8 students from an exclusive sectarian school for girls in Quezon City. Quantitative data were collected from the pretest and posttest results of the Biology Concept Understanding Test (BCUT) and Learner Autonomy in Biology Scale (LABS). Whereas, qualitative data were retrieved from an online questionnaire, journal entries, and researcher's field log. Analysis of data showed that IW period with metacognitive prompts was significant in improving the readiness of students for self-directed learning. Furthermore, there was a significant difference in the BCUT scores of participants before and after the intervention in favor of the posttest. This finding indicates that the IW period with metacognitive prompts may have contributed to the concept understanding of student. It was noted, however, that there was no significant improvement in the LABS score after the intervention. The simple linear regression analysis showed that autonomy is not a positive predictor of concept understanding in Biology. Through student participants described IW period with metacognitive prompts as a helpful tool in planning, monitoring, and completing learning tasks in Biology, they did not recognize it as beneficial in understanding biological concepts. It is recommended that the prompts during IW period contain both metacognitive and learning strategy prompts to develop autonomy and concept understanding.